Morphological and molecular identification of arrhenotokous strain of Diglyphus wani (Hymenoptera, Eulophidae) found in China as a control agent against agromyzid leafminers - Su-Jie Du (Pensoft Publishers, 2021)
Diglyphus species are ecologically and economically important on agromyzid leafminers. In 2018, a thelytokous species, Diglyphus wani Liu, Zhu & Yefremova, was firstly reported and described. Subsequently, the arrhenotokous D. wani were discovered in Yunnan and Guizhou Provinces of China. We compared the morphological characteristics of thelytokous and arrhenotokous strains. However, the females of two strains had a strongly similar morphology and showed subtle differences in fore- and hind-wings. The difference was that forewing of arrhenotokous female was with denser setae overall, showing that costal cell with 2 ~ 4 rows of setae on dorsal surface and the setae of basal cell with 15 ~ 21 hairs and forewing of thelytokous female was with two rows of setae on dorsal surface and basal cell with 10 ~ 15 hairs generally. The setation beneath the marginal vein of the hind-wing of arrhenotokous female is denser than the same area of thelytokous female. To explore the genetic divergence between thelytokous and arrhenotokous strains of D. wani, the mitochondrial and nuclear gene were applied and sequenced. The polygenic analyses revealed that two strains can be distinguished by COI, ITS1 and ITS2. The mean sequence divergence between the two strains was 0.052, 0.010 and 0.007, respectively. Nevertheless, the 28S gene was unfeasible due to its containing a sharing haplotype between different strains. The two strains of D. wani are dominant parasitoids against agromyzid leafminers and such effective discernible foundation provides future in-depth studies on biological characteristics, along with insight into field application of two strains of D. wani.